(untitled) (Social Science Review, 2022)
Following eviction from several brothels, the sex workers of Bangladesh started their movement in the 1990s. Through their activism, the sex workers demanded their rights. Just about the same period, NGOs were working with the sex workers on HIV-related issues focusing on their empowerment alongside condom promotion. Through their involvement with the NGOs and HIV programmes, the sex workers have gained visibility in the public domain. Due to availability of funds from the NGOs sex workers were able to participate in international gatherings where they learnt about sex work as a form of labour. In claiming their rights, the sex workers exhibited active agency which corresponds to pro-sex work feminist discourse. However, despite some positive outcomes of the sex workers’ movement, the demand for their rights became blurred as they got more and more involved in the arena of HIV. Using a feminist methodology, this article draws on the experiences of women’s rights activists, sex worker activists as well as sex workers to understand the trajectory that the struggles of the sex workers have taken place due to their involvement with NGOs and HIV-related programmes. In doing so it explores the nature of such interrelationship from the perspective of the global south. Social Science Review, Vol. 38(1), June 2021 Page 157-174